2021
DOI: 10.1002/hep.31735
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Metabolic and Transcriptomic Signature of PNPLA3‐Associated NASH

Abstract: A bout 30% of the adult population in the USA is afflicted with NAFLD. Approximately 20%-25% of patients with NAFLD have the progressive subtype of NAFLD: NASH. The cardinal features of NASH on liver histology include steatosis, lobular inflammation, and ballooning with or without perisinusoidal fibrosis. (1) Currently, NASH is the second-leading indication for liver transplant in the USA, and is the fastest rising etiology leading to rising rates of HCC in the USA. The mechanistic understanding of why some pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In the last decade, an increasing number of events have demonstrated that PNPLA3 rs738409 polymorphism is closely associated with hepatic fat accumulation, ALD, NASH, cirrhosis, and HCC [15,17,[25][26][27][28]. It has been further reported that the PNPLA3-I148M variant promotes the progression of fibrosis by modulating retinol metabolism and upregulating the pro-inflammatory cytokines JNK and AP-1 in HSCs or LX-2 cells upon different types of nutritional status, respectively [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, an increasing number of events have demonstrated that PNPLA3 rs738409 polymorphism is closely associated with hepatic fat accumulation, ALD, NASH, cirrhosis, and HCC [15,17,[25][26][27][28]. It has been further reported that the PNPLA3-I148M variant promotes the progression of fibrosis by modulating retinol metabolism and upregulating the pro-inflammatory cytokines JNK and AP-1 in HSCs or LX-2 cells upon different types of nutritional status, respectively [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has supported the notion that FC load is closely related to mitochondrial dysfunction in NASH [25,26]. On this basis, we further evaluated mitochondrial function in PNPLA3-I148I and -I148M stably expressed LX2 cells.…”
Section: Pnpla3-i148m Disrupts the Function Of Mitochondrialmentioning
confidence: 91%
“…In our patient cohort, we found that the PNPLA3/rs738409 variant was significantly associated with liver fibrosis in unadjusted and adjusted models. The G allele of PNPLA3/rs738409 produces a mutation, I184 M. After activation of STAT3 (signature of transducer and activator of transcription 3), this allele is involved in the persistent inflammatory response associated with liver fat accumulation and NAFLD/NASH [21]. In a mouse model of NASH, development of steatohepatitis and fibrosis is accelerated and its severity worsened by overexpression of human PNPLA3I148 M [22].…”
Section: Discussionmentioning
confidence: 99%
“…While minimizing reliance on live animal models, the results show that I148M variants lead to increased lipid accumulation and susceptibility to hepatotoxins ( Tilson et al, 2021 ). Previous studies have demonstrated that PNPLA3(148M) variation is associated with a variety of liver diseases, including MAFLD, non-alcoholic steatohepatitis (NASH), fibrosis, cirrhosis, and hepatocellular carcinoma (HCC) ( Dhar and Loomba, 2021 ), and increases the risk of liver-related death ( Grimaudo et al, 2020 ; Stender and Loomba, 2020 ). The genetic locus has been identified as having the most powerful role in increasing liver disease ( Shang and Mashek, 2020 ).…”
Section: Major Genetic Predisposition In Mafldmentioning
confidence: 99%